Film sound theory and practice - Weis, Elisabeth 1966- (Columbia Univ. Press, 1985)
The only comprehensive book on film sound, this anthology makes available for the first time and in a single volume major essays by the most respected film historians, aestheticians, and theorists of the past sixty years. In addition, it provides useful models for the analysis of sound stylistics in the form of case studies of a number of the most important sound films ever made. It is a compact primer/handbook which reviews in a coherent, rigorous, yet eminently accessible way the techniques and practices of sound filmmaking from initial recording to final playback in the theater. The book contains essays by Douglas Gomery, Barry Salt, Rick Altman, Mary Ann Doane, S. M. Eisenstein, V. I. Pudovkin, Rene' Clair, Rudolf Arnheim, Bela Balazs, Siegfried Kracauer, Christian Metz, David Bordwell, Kristin Thompson, Noël Burch, Arthur Knight, Lucy Fischer, Noël Carroll, Alan Williams, Fred Camper, and others. Essays deal in detail with such filmmakers as Lubitsch, Clair, Mamoulian, Vertov, Lang, Pabst, Stahl, Welles, Hitchcock, Renoir, Bresson, Godard, Altman, and Coppola.